DEVELOPING ANDROID APPLICATIONS BASED ON CULTURE IN TANGERANG FOR SOCIAL SCIENCE SUBJECT AT GRADE IV OF SDN PABUARAN 1 TANGERANG - Astri; Ana Nurhasanah; Ikman Nur Rahman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop an android application based on the culture of Tangerang and to determine the feasibility of the application. This study utilized the R&D research method on the Brog and Gall development design modified by Sugiyono following six stages: 1) Problem analysis; 2) Data collection; 3) Product design; 4) Expert validation; 5) Design revision, and 6) Product trial. This was conducted in class IVB SDN Pabuaran 1 Tangerang. The feasibility of the product was examined by several experts such as education experts, material experts, and media experts. The validation result from media experts obtained an average score of 92% with the "Very Feasible" category. The validation result from material experts got an average score of 87% with the "Very Feasibility" category. Then, the validation result from education experts obtained an average score of 91% with the "Very Feasibility" category. After that, the results of the students' response on a limited trial obtained a percentage of 88% with the "Very Good" category. Based on the results of the study, the final product in the form of an android application based on the culture of Tangerang City was suitable for learning the social science subject at grade IV of elementary school.